MATHEMATICAL MODELING OF SHALINESS INFLUENCE ON THE ELASTIC PROPERTIES OF VOLYNO-PODILLYA COMPOUND LIMESTONES - BEZRODNA, I.; BEZRODNYI, D.; KUZMENKO, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The type and clay concentration, structure of pore space, fluid saturation, orientation of cavities and inclusions influences on the effective acoustic and elastic properties of carbonate reservoir-rocks of the Volyno-Podillia is investigated.